1985
DOI: 10.1002/pssa.2210890105
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electrical Properties of the LaCo1−xMnxO3 and LaCo1−xFexO3 Systems

Abstract: Structure and electrical properties of two perovskite systems LaCo1−xMnxO3 and LaCo1−xFexO3 (0 ≦ x ≦ 1) are described. A phenomenological phase diagram based on the relation between cation radii rA, rB and the void radius at the A‐site is proposed that rationalises most of the existing structural data. Results on measurements of electrical resistivity and Seebeck coefficient are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…For the ORR data of Suntivich et al [22], the activity trend matches that of the typical conductivity of the used LaBO 3 perovskites. Moreover, the previously found local activity maximum of Mn relative to Cr and Fe in all data sets is also mirrored in the conductivity data [72,73,80,81]. The detrimental effect of insufficient conductivity is most pronounced in the thin film study of Stoerzinger et al [60], where no activity was detected for LaCrO 3 and LaFeO 3 in the investigated voltage range.…”
Section: Effect Of Chemical Substitution On Activitysupporting
confidence: 69%
See 1 more Smart Citation
“…For the ORR data of Suntivich et al [22], the activity trend matches that of the typical conductivity of the used LaBO 3 perovskites. Moreover, the previously found local activity maximum of Mn relative to Cr and Fe in all data sets is also mirrored in the conductivity data [72,73,80,81]. The detrimental effect of insufficient conductivity is most pronounced in the thin film study of Stoerzinger et al [60], where no activity was detected for LaCrO 3 and LaFeO 3 in the investigated voltage range.…”
Section: Effect Of Chemical Substitution On Activitysupporting
confidence: 69%
“…Substitution of the B-site in LaBO 3 drastically changes the expected bulk conductivity betweeñ 1 µS/cm for Fe [72] to~1 S/cm for Ni [73] (Figure 2e), while it has a clear maximum for La 1−x Sr x MnO 3 [63] (Figure 2f). No discernable trend could be identified for substitution of the A-site from La to Dy [74][75][76][77][78][79][80] (Figure 2g) under the caveat that some of the data was only available for temperatures >300 K (Table A2).…”
Section: Effect Of Chemical Substitution On Activitymentioning
confidence: 96%
“…Table 1. By comparing the obtained results with experimental values, we found that LDA approximation methods were more applicable for calculating bonds lengths 39 and lattice parameters. 40 The Co-O bond length was 1.925Å and the lattice parameter was 5.446Å as calculated by CA-PZ, which approached the experimental values (1.929Å and 5.444Å); however the electron distributions were strongly restricted by LDA approximation, and the absolute value of the forbidden band width and the system binding energy were not suitable for analysis by LDA.…”
Section: Introductionmentioning
confidence: 92%
“…Some studies appear to be less accurate and report two single phase regions at room temperature without a two-phase region. For instance both Narasimhan et al [71] and Jia et al [72]…”
Section: Lafe 1-x Co X O 3-δ Systemsmentioning
confidence: 99%